The Effect of Work Environment and Competencies on Employee Performance at the Class III Port Administration Office in Barus, Central Tapanuli - Chairul Chairul; Anita Maharani; Heriani Heriani (International Journal Labs, 2026)
This study examines the influence of work environment and employee competence on employee performance at the Class III Port Administration Office in Barus, Central Tapanuli. The research is motivated by the declining performance of employees, as indicated by low service satisfaction among port users, which highlights the importance of improving organizational factors that support employee productivity. The objective of this study is to analyze both the partial and simultaneous effects of work environment and competence on employee performance. A quantitative associative approach with an explanatory design was employed, involving 32 employees selected using total sampling. Data were collected through questionnaires and interviews and analyzed using multiple linear regression with SPSS. The results show that competence (? = 0.401; t = 5.405; p < 0.05) and work environment (? = 0.328; t = 4.220; p < 0.05) have a positive and significant effect on employee performance. Simultaneously, both variables significantly influence performance (F = 31.247; p < 0.05) with a coefficient of determination (R²) of 0.679, indicating that 67.9% of performance variation is explained by the model. The study concludes that improving employee competence and creating a conducive work environment are essential strategies to enhance employee performance and service quality